DEVELOPING COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS BASED ON A REFLEXIVE APPROACH: MECHANISMS AND MODELING - Ruziyev Azimjon Erkinovich (International Journal of Literature and Language Studies, 2026)
This article systematically investigates the mechanisms and structural modeling involved in developing the communicative competence of future teachers through a reflexive approach. In modern higher pedagogical education, shifting from a traditional knowledge-based paradigm to a competence-oriented framework requires future educators to possess not only linguistic and pedagogical skills but also deep-rooted socio-psychological agility. This study delineates the structural components—cognitive, motivational, operational, and reflexive—and establishes distinct criteria for assessing reflexive-communicative competence. Furthermore, the paper analyzes the internal psychological mechanisms (identification, empathy, self-analysis) and external pedagogical mechanisms (feedback loops) that accelerate this development. A comprehensive pedagogical model designed for higher education institutions is introduced, showing how structured reflective practices optimize communicative efficacy. The findings suggest that integrating structured reflexive practices into the curriculum significantly enhances pedagogical interaction and professional self-awareness.